Memelihara Kebersihan Tangan Mendukung Kesehatan Anak di SD Watdek Maluku Tenggara - Agne Batmomolin; Wa Rina; Rahil Metanfanuan (Yayasan Literasi Sains Indonesia, 2024)
Hands are exposed to many microorganisms because human activities are dominated by hands. Therefore, hands are the most common place to transmit disease. Maintaining hand hygiene means maintaining health. School age children are known to be very active, therefore they are susceptible to various infectious diseases. At the same time, school age is the right time to provide health education about maintaining health. Maintaining hand hygiene is a simple and easy way to do it but has a big impact, namely maintaining overall body health. The implementation of community service activities is based on health promotion. The activity stage is preparation with the school, while the implementation stage is providing health education followed by a demonstration and re-demonstration of the correct way to wash hands to students in grades 1 and 2 of Watdek Elementary School, Southeast Maluku. At the end of the activity, the service team handed over a poster of steps for washing hands to the teacher to be placed in each class near the hand washing station. Hopefully this activity can build the habit of maintaining hand hygiene which will be implemented at all times by students at Watdek Elementary School, Southeast Maluku, to support their health